Exploration in Start-Up Organization through Qualitative Content Analysis - Djati, Adhi Waluyo; Febriansyah, Hary (Journal of Business and Management, 2015)
Abstract — A startup organization is a recently made organization that is in the development stage and still looking into the potential markets. Every startup has its own plan of action and different structures. The objects of the research are Goodism (est. 2013), Woodka (est. 2013) and Humblezing (est. 2010). This research is a qualitative study which uses one of the organizational development theories, which is appreciative inquiry (AI) which focuses on the organization’s learning and positive presumption from its member. Job design factor and performance management system components are the literature that will be guided this study. Moreover, the researcher position in this research is the conductor of the appreciative inquiry method. Data collection is using the qualitative approach, which are semi-structured interview. The data will be collected through doing the semi-structured interview with the Board of Directors’ in each company. The questions that will be answered by the Board of Directors’ are following the appreciative inquiry processes. The data analysis is using the qualitative content analysis with deductive approach. This research finds that in making the job design, Goodism should decide the objectives that will be attained in the working period, every member has to decide their own portion of work, the member is working based on their interest, also the implementation of working hour and rotation between divisions seen as appropriate to be implemented. In making performance management system, Woodka should consider that every member should be involved in planning the target and deadline and relating their own activities which interconnected with other activities, monthly review seen as the appropriate one because it can be customized with the production schedule, implementation of feedback can be face-to-face and the reward system that may be conducted is rewarding the good performance punishing the bad performance by the member. In making the performance management system, Humblezing should consider that the control system to the job that is ongoing is essential, the target and deadline can be derived from the company’s objective and the measurement of the performance and return for a job should be clear, monthly & weekly review can be done to detect the problem in a job faster and every member has got to know the other member’s work progress, and monetary (such as bonus salary) and non-monetary (such as member trip) compensation may be conducted.Keywords: organizational development, appreciative inquiry, job design, performance management system